Associations of language‐based bedtime routines with early cognitive skills and academic achievement: A follow‐up from kindergarten to middle school. (5th May 2021) - Câmara‐Costa, Hugo; Pulgar, Salomé; Cusin, Françoise; Labrell, Florence; Dellatolas, Georges
Abstract : Objective: This study aimed to investigate the extent to which language‐based bedtime routines (LBR) reported by parents before kindergarten were associated with early cognitive skills at kindergarten and subsequent academic achievement in typically developing children. Method: We followed a community‐based sample of 664 French‐speaking adolescents from kindergarten (5–6 years) to the end of middle school (15 years). Kindergarten measures included a parental questionnaire aimed at assessing the presence or absence of any kind of LBR, such as storytelling, looking at children's books, reading a story, listening to songs, or singing nursery rhymes, as well as family contextual characteristics. Children also performed standardized assessments of oral language, pre‐reading skills, and non‐verbal reasoning. In middle school, children sat a national diploma typically used as an indicator of general academic achievement in Grade 9. Results: After adjusting for family characteristics, the presence of language‐based bedtime routines (57%) predicted cognitive–academic skills in kindergarten, and was positively associated with academic achievement at Grade 9, related to the beneficial effect on children's vocabulary in kindergarten. Conclusion: The presence of language‐based bedtime routines may provide an indicator of positive parental behaviour including exposure to literacy activities, contributing to children's early cognitive development and subsequent academic achievement.